2016
DOI: 10.1039/c5nr07206a
|View full text |Cite
|
Sign up to set email alerts
|

Mucin-mediated nanocarrier disassembly for triggered uptake of oligonucleotides as a delivery strategy for the potential treatment of mucosal tumours

Abstract: This work demonstrates gastric mucin-triggered nanocarrier disassembly for release of antisense oligonucleotides and consequent unassisted cellular entry as a novel oral delivery strategy. A fluorescence activation-based reporter system was used to investigate the interaction and mucin-mediated disassembly of chitosan-based nanocarriers containing a 13-mer DNA oligonucleotide with a flanked locked RNA nucleic acid gapmer design. Gastric mucins were shown to trigger gapmer release from nanocarriers that was dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…3 Notably, the mucus layer, which covers the intestinal epithelium as the first barrier, creates obstacles for the transportation of nanomedicines into blood circulation through the intestinal mucosa. 4,5 As the key component, proteoglycans in the mucus layer interact with each other to form a reticular structure, thus protecting the gastrointestinal (GI) tract against the access of exogenous substances including many types of nanomedicines. 6−9 Because of the negative effects of the mucus layer on nanomedicine transportation, multiple functional nanomedicines have been fabricated to overcome the obstacles.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Notably, the mucus layer, which covers the intestinal epithelium as the first barrier, creates obstacles for the transportation of nanomedicines into blood circulation through the intestinal mucosa. 4,5 As the key component, proteoglycans in the mucus layer interact with each other to form a reticular structure, thus protecting the gastrointestinal (GI) tract against the access of exogenous substances including many types of nanomedicines. 6−9 Because of the negative effects of the mucus layer on nanomedicine transportation, multiple functional nanomedicines have been fabricated to overcome the obstacles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Over the last several decades, the successful introduction of nanotechnology has brought more oral nanomedicines into the market, improving the bioavailability or therapy efficacy of drugs; meanwhile, more oral nanomedicines are still in clinical trials and preclinical studies . Notably, the mucus layer, which covers the intestinal epithelium as the first barrier, creates obstacles for the transportation of nanomedicines into blood circulation through the intestinal mucosa. , As the key component, proteoglycans in the mucus layer interact with each other to form a reticular structure, thus protecting the gastrointestinal (GI) tract against the access of exogenous substances including many types of nanomedicines. Because of the negative effects of the mucus layer on nanomedicine transportation, multiple functional nanomedicines have been fabricated to overcome the obstacles. Mucoadhesive polymers have been adopted to improve the residence time of nanoparticles in the GI tract .…”
Section: Introductionmentioning
confidence: 99%
“…Mater. 2020, 32,1901935 Intestine asRNA (Gapmers) CS NP [142] Abbreviations in the table; HA hyaluronic acid; NIPAAm-co-Aam poly(N-isopropylacrylamide-co-acrylamide); P[MAA-co-NVP] poly(methacrylic acid-co-N-vinyl-2-pyrrolidone); CMC-G6P carboxymethyl cellulose-glucosamine 6-phosphate.…”
Section: Dna and Rnamentioning
confidence: 99%
“…The pharmaceutical effect of the model peptide was detected even 120 h after the administration by the chitosan‐liposome formulation . Martirosyan et al reported exciting results on chitosan‐based nanocarriers . Their sub‐200 nm sized chitosan particles dissembled in the presence of porcine gastric mucin and released the transported cargo.…”
Section: Mucoadhesionmentioning
confidence: 99%
“…[49] Martirosyan et al reported exciting results on chitosanbased nanocarriers. [50] Their sub200 nm sized chitosan particles dis sembled in the presence of porcine gastric mucin and released the transported cargo. It was even shown that coating/blending the surface with chitosan was already sufficient to enhance mucoadhesion of a given nano/microparticle.…”
Section: Cationic Polymersmentioning
confidence: 99%